Multidrug-resistant and epidemic clones of Escherichia coli from natural beds of Venus clam. (October 2016) - Vignaroli, C.; Di Sante, L.; Leoni, F.; Chierichetti, S.; Ottaviani, D.; Citterio, B.; Biavasco, F.
Abstract: Epidemic Escherichia coli clones have been recovered in marine sediment along the coast of Marche, an Adriatic region in central Italy. In the present study, E. coli strains from the clam Chamelea gallina, sampled from seven natural beds in the same area, were detected. Selected E. coli isolates from all sampling sites were screened for antimicrobial susceptibility, genetic diversity and correlation. The majority (60%) belonged to phylogroups A or B1, 31% to the other groups (B2, C, D, E, F), 8% to cryptic clades, and 1% were untypable. Moreover, 33.3% of isolates were resistant to at least one drug and 11% were multidrug resistant (MDR). The most common resistance was to tetracycline, ampicillin, and streptomycin. No clonality was detected, but the strains' high genetic heterogeneity pointed at multiple sources of microbiological contamination. MLST analysis found potentially pathogenic and even epidemic MDR strains in clams collected in class A (ST746 and ST46) and class B (ST393, ST58 and ST131) areas, indicating that strains of clinical origin are detectable in clams. These data highlight that eating raw or lightly cooked clams may pose a health risk if purification is not performed or is ineffective. Highlights: Multidrug-resistant Escherichia coli isolates of clinical origin from Venus clam. Potentially pathogenic strains recovered in clams from class A harvesting areas. Health risks from consumption of raw or lightly cooked contaminated clams.